Knowledge of menstruation and fertility among adults in rural Western Kenya: Gaps and opportunities for support - Ayodo, George; Onyango, George O. (PLOS ONE, 2020)
An understanding of menstruation and its relationship to fertility can help women know the gestational age of any pregnancies, and thus identify preterm births. It can also help women avoid unintended pregnancies. However, little is known about women, and especially men’s, menstruation and fertility knowledge, outside of research on adolescent girl’s stigma, and in low and middle income countries(LMIC). Additionally, little is known about practices surrounding the tracking of menstruation and fertility, and how, if at all, women would like to be supported in this. This research is the first phase in adapting a support tool for women in a LMIC, using an implementation science approach to understand relevant cultural needs. We explored women and men’s understanding of the relationship between menstruation and fertility, and their interest in support tools, through in-depth qualitative interviews in rural western Kenya. We interviewed 45 adult men, adult women and adolescent women all who had children in 2018.Wefoundhighlevelsof misinformation about menstruation and fertility, with most respondents not knowing the correct times when a woman could become pregnant. Common sources of knowledge included friends/family and school. Few women got information from health providers, even when they were at a facility already for care. There were mixed feelings from women about wanting support from male partners regarding tracking menstruation. While women were interested in a tool that could help them track their menstruation and pregnancies, they had privacy concerns about a mobile health app approach and preferred simpler calendar based tools. This study provides evidence for the high need for correct menstruation information among both men and women, and not only for adolescents. It also suggests that despite the international health community’s enthusiasm for mobile health solutions, that approach might not be most appropriate for this topic and setting.